2013
DOI: 10.5039/agraria.v8i1a1679
|View full text |Cite
|
Sign up to set email alerts
|

Uso de biofertilizantes e águas salinas em plantas de Licopersicon pimpinellifolium L.

Abstract: RESUMOUm experimento foi conduzido em abrigo telado do Departamento de Solos do Centro CCA -UFPB, Areia, PB, no período de maio a junho de 2008, com o objetivo de avaliar os efeitos de dois tipos de biofertilizantes no desenvolvimento da cultura do tomateiro-cereja sob irrigação com águas salinas. O delineamento experimental foi inteiramente casualizado em esquema fatorial 5 x 3, com seis repetições, referentes aos valores de condutividade elétrica da água de irrigação: 0,5; 1,0; 2,0; 3,0 e 4,0 dS m -1 , no so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
1
3
0
2
Order By: Relevance
“…The interaction between water salinity and the chemically enriched bovine biofertilizer had significant effects on soil salinity and on the growth and quality of jackfruit seedlings by the end of the experiment (Table 3). Similar soil and plant responses were recorded by Medeiros et al (2013) and Lima Neto et al (2018), when they concluded that the interaction of saline water and biofertilizer, enriched with cow's milk, molasses and agricultural gypsum, exerted significant effects on the growth and biomass of cherry tomato plants and the formation of tamarind seedlings. Soil salinity increased linearly to levels of 0.3310 and 0.6406 per unit increase of the electrical conductivity of the irrigation water in treatments without and with enriched biofertilizer, respectively, with soil showing superiority with the organic input ( Figure 1).…”
Section: Contentssupporting
confidence: 65%
See 1 more Smart Citation
“…The interaction between water salinity and the chemically enriched bovine biofertilizer had significant effects on soil salinity and on the growth and quality of jackfruit seedlings by the end of the experiment (Table 3). Similar soil and plant responses were recorded by Medeiros et al (2013) and Lima Neto et al (2018), when they concluded that the interaction of saline water and biofertilizer, enriched with cow's milk, molasses and agricultural gypsum, exerted significant effects on the growth and biomass of cherry tomato plants and the formation of tamarind seedlings. Soil salinity increased linearly to levels of 0.3310 and 0.6406 per unit increase of the electrical conductivity of the irrigation water in treatments without and with enriched biofertilizer, respectively, with soil showing superiority with the organic input ( Figure 1).…”
Section: Contentssupporting
confidence: 65%
“…There are few reports on the use of bovine biofertilizer, chemically enriched with cow's milk, molasses and agricultural gypsum, in plants irrigated with non-saline water and water with increasing salinity. Medeiros et al (2013) showed chemically enriched biofertilizer increased biomass in tomato-cherry (Licopersicon pimpinellifolium), under irrigation with low and high salinity water. For the growth and quality of tamarind seedlings (Tamarindus indica) irrigated with salinity water ranging from 0.5 to 6.0 dS m -1 , Lima Neto et al (2018) concluded that enriched biofertilizer, despite not exceeding common biofertilizer, exerted a significantly higher effect on the soil without any of the inputs.…”
Section: Introductionmentioning
confidence: 99%
“…Os níveis salinos das águas de irrigação foram preparados a partir da diluição de uma água de barragem fortemente salina (CEa = 26,5 dS m -1 ) em água não salina de 0,5 dS m -1 (Medeiros et al, 2013). Substrato utilizado foi um Neossolo Regolitico coletado na camada de 0-20 cm.…”
Section: Metodologiaunclassified
“…Dois dias antes da semeadura, o biofertilizante foi diluído em água na proporção 1:1 e aplicado em volume equivalente a 10% do volume do substrato (350 mL). Os níveis salinos das águas de irrigação foram preparados a partir da diluição de uma água de barragem fortemente salina (CEa = 25,4 dS m -1 ) em água não salina de 0,5 dS m -1 (Medeiros et al, 2013). Substrato utilizado foi um Neossolo Regolitico coletado na camada de 0-20 cm (Santos et al, 2006).…”
Section: Metodologiaunclassified